The core emergency ultrasound curriculum project: A report from the Curriculum Working Group of the CAEP Emergency Ultrasound Committee. Issue 2 (19th June 2017) - Olszynski, Paul; Kim, Dan; Chenkin, Jordan; Rang, Louise
Abstract : Emergency ultrasound (EUS) is now widely considered to be a "skill integral to the practice of emergency medicine." 1 The Canadian Association of Emergency Physicians (CAEP) initially issued a position statement in 1999 supporting the availability of focused ultrasound 24 hours per day in the emergency department (ED). 2